2021
DOI: 10.1080/1461670x.2021.1929416
|View full text |Cite
|
Sign up to set email alerts
|

From The Daily Show to Last Week Tonight: A Quantitative Analysis of Discursive Integration in Satirical Television News

Abstract: Satirical news shows constitute an innovative hybrid genre that mixes regular news and fiction. The discursive integration hypothesis posits that the defining characteristic of satirical news shows is that news and fiction elements are integrated such that boundaries between the preexisting genres have blurred. The current study quantitatively tests this hypothesis on both longrunning American shows such as The Daily Show and more recent shows such as Last Week Tonight. We collected transcripts of fifteen sati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…At the international level, Gray et al (2009) acknowledge that, although satirical television content is intended to give citizens a better "ability to watch the political process at work," it often achieves the opposite effect and "attract[s] more ridicule than ardent viewers" (p. 3). Similarly, some research corroborates the blurring of the boundaries between fiction and regular news found in shows such as satirical news programs, which has been quantitatively tested both in long-running American programs such as The Daily Show (Comedy Central, 1996) and more recent shows such as Last Week Tonight with John Oliver (HBO, 2014), which are characterized by their hybrid nature and by the inclusion of opinion (Brugman et al, 2021).…”
Section: Introduction 1spanish Audiences and Infotainment Comedymentioning
confidence: 69%
“…At the international level, Gray et al (2009) acknowledge that, although satirical television content is intended to give citizens a better "ability to watch the political process at work," it often achieves the opposite effect and "attract[s] more ridicule than ardent viewers" (p. 3). Similarly, some research corroborates the blurring of the boundaries between fiction and regular news found in shows such as satirical news programs, which has been quantitatively tested both in long-running American programs such as The Daily Show (Comedy Central, 1996) and more recent shows such as Last Week Tonight with John Oliver (HBO, 2014), which are characterized by their hybrid nature and by the inclusion of opinion (Brugman et al, 2021).…”
Section: Introduction 1spanish Audiences and Infotainment Comedymentioning
confidence: 69%
“…The two programs are similar in format and style, consisting of satirical segments presented by a host behind a news desk in front of a live audience. Since the programs include investigative and interpretative segments that also address issues outside the traditional news spotlight, they could be described as opinion news formats (Brugman et al 2021), and they are both examples of the satire subgenre journalistic news satire (Koivukoski and Ödmark 2020). In this study, episodes of the satirical programs were subjected to a content analysis with both quantitative and qualitative aspects.…”
Section: Methodsmentioning
confidence: 99%
“…Sardinha and Pinto (2019) identified the dimensions of variation across American television programs. Brugman et al (2021) collected transcripts of satirical news shows, regular news shows, and fiction shows to identify register dimensions, and patterns in linguistic features unique to genres, which we used to determine the presence of discursive integration. Pinto and Sardinha (2014) analyzed the discourse evolution of American films from 1930 to 2010, identified 7 dimensions, and used ANOVA to analyze the variation.…”
Section: A Research On Multi-dimensional Analysismentioning
confidence: 99%